INFORMAL ELDERLY CARE IN KAZAKHSTAN: EFFECTS ON THE PROFESSIONAL DEVELOPMENT OF WOMEN - Balagozinova, Anel (Nazarbayev University School of Sciences and Humanities, 2025)
The thesis explores the informal elderly care system in Kazakhstan. The main focus of the work is the experiences of women who perform caretaking responsibilities in their families. It examines the effects of caregiving on emotional and physical well-being, professional development and their everyday lives. The research is based on qualitative research methods: semi-structured interviews and digital observation on online platforms. These methods allowed the researcher to explore caregiving experiences and existing discussions and public narratives about elderly care. The analysis of data is based on feminist theories of care (Tronto, Kittay) and social reproduction theory (Fraser, Folbre). These theories allow us to investigate caretaking practices and their role in society and help to explain why caregiving is associated with duties and why this duty is often undervalued. Moreover, the concept of double burden (Hochschild) is one of the central to this work, drawing attention to how women are often expected to perform both paid work and unpaid caregiving responsibilities, which causes stress, physical and emotional exhaustion. According to the findings, the informal elderly care system in Kazakhstan is shaped by gender norms and is affected by societal expectations, thus resulting in caregivers’ career opportunities, social isolation, and high levels of stress. However, for most women caregiving for elderly is also associated with positive aspects, such as strengthening of family bonds, and a sense of fulfilled duty. This study illustrates the complex nature of caregiving and the burden of caregiving that is placed on women, highlighting the need for institutional support in the care practices and a broader recognition of care work in society.
Keywords: type of access: embargo; informal care; costs of informal care; gender roles; double burden; emotional labor; elderly care